2019
DOI: 10.1063/1.5114871
|View full text |Cite
|
Sign up to set email alerts
|

Non-leaky longitudinal acoustic modes in ScxAl1-xN/sapphire structure for high-temperature sensor applications

Abstract: Multilayered structures based on wide bandgap nitride piezoelectric thin films are very attractive for high-temperature surface acoustic waves (SAW) sensor applications. In this respect, scandium aluminium nitride (ScAlN) films are of particular interest as they combine enhanced piezoelectric properties and slower acoustic waves velocities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A previous work, including a simulation study, revealed that the three observed modes respectively correspond to a Rayleigh SAW, a shear horizontal (SH) SAW, and a high-velocity longitudinal leaky SAW. The latter can show low attenuation coefficients if a careful choice of the film thickness, as well as the electrode nature and thickness, is made [30]. The experimental velocities of these three modes are of 4680 ms −1 , 6045 ms −1 and 9945 ms −1 respectively.…”
Section: Saw Characterization Results and Numerical Simulationmentioning
confidence: 98%
See 4 more Smart Citations
“…A previous work, including a simulation study, revealed that the three observed modes respectively correspond to a Rayleigh SAW, a shear horizontal (SH) SAW, and a high-velocity longitudinal leaky SAW. The latter can show low attenuation coefficients if a careful choice of the film thickness, as well as the electrode nature and thickness, is made [30]. The experimental velocities of these three modes are of 4680 ms −1 , 6045 ms −1 and 9945 ms −1 respectively.…”
Section: Saw Characterization Results and Numerical Simulationmentioning
confidence: 98%
“…The electromechanical coupling k 2 was estimated from the extracted difference between resonant and anti-resonant frequencies. The same numerical technique was previously used to explain the nature of the acoustic modes observed experimentally and predict the existence of low-attenuated high-velocity longitudinal leaky SAWs in ScxAl1-xN/sapphire with optimized film and electrode thicknesses [30]. The electromechanical coupling k 2 of SAW modes propagating in Sc x Al 1−x N/sapphire structure generally increases with the Sc x Al 1−x N thickness, due to the better confinement of displacements in the piezoelectric film.…”
Section: Saw Characterization Results and Numerical Simulationmentioning
confidence: 99%
See 3 more Smart Citations